2019
DOI: 10.1002/jccs.201900147
|View full text |Cite
|
Sign up to set email alerts
|

Dinitrosyl iron complexes: From molecular electrocatalysts to electrodeposited‐film electrodes for hydrogen evolution reaction

Abstract: Clean and large‐scale production of hydrogen via water splitting triggered by active, robust, and low‐cost electrocatalysts is a promising and sustainable strategy for energy conversion and storage. In this study, a series of four‐coordinated chelating amine‐bound {Fe(NO)2}10 dinitrosyl iron complexes (DNICs) [(L)Fe(NO)2] were synthesized to investigate how the electronic structure of [Fe(NO)2] unit of DNICs was tailored to promote the electrocatalytic hydrogen evolution reaction (HER) triggered by the homogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Complexes 99 , 142 and 153 were incorporated into heterogeneous electrodes to constitute remarkable HER catalysts, capable of reducing protons from water. Liaw and coworkers used the {Fe­(NO) 2 } 9 /{Fe­(NO) 2 } 10 redox couple in DNICs to design complexes for a solid-state hydrogen evolution cathode. ,, The low-cost PMDTA-bound DNIC 142 , deposited on an electrode, exhibits a low onset potential of -717 mV versus SHE in a neutral 1.0M KCl solution to generate H 2(g) from water . The catalytic activity of DNICs can be further tuned by ligand design.…”
Section: Dinitrosyl Iron Complexes (Dnics)mentioning
confidence: 99%
See 1 more Smart Citation
“…Complexes 99 , 142 and 153 were incorporated into heterogeneous electrodes to constitute remarkable HER catalysts, capable of reducing protons from water. Liaw and coworkers used the {Fe­(NO) 2 } 9 /{Fe­(NO) 2 } 10 redox couple in DNICs to design complexes for a solid-state hydrogen evolution cathode. ,, The low-cost PMDTA-bound DNIC 142 , deposited on an electrode, exhibits a low onset potential of -717 mV versus SHE in a neutral 1.0M KCl solution to generate H 2(g) from water . The catalytic activity of DNICs can be further tuned by ligand design.…”
Section: Dinitrosyl Iron Complexes (Dnics)mentioning
confidence: 99%
“…Additional wound healing effects were seen by Yuan, Lu, Liaw and Wang using a mercaptoethanol-bound DNIC to promote angiogenesis and wound healing in diabetic mice by a sustained release of NO, activating the NO-sGC-cGMP pathway (see Section ). This same complex was also used to regulate the IIS, AMPK and mitochondrial signaling pathways in C. elegans by O 2 -triggered release of NO • to extend the lifespan of this organism …”
Section: Dinitrosyl Iron Complexes (Dnics)mentioning
confidence: 99%
“…The elemental composition and chemical state of the active particles were further characterized by X-ray photoelectron spectra (XPS) (Figure S11). [51][52][53] The Fe 2P spectrum shows two intense peaks (2P 1/2 and 2P 3/2 ) and two broad peaks (shark satellite signal). Fe 2P 3/2 appears binding energy at 710.0 and 711.8 eV attribute to Fe 2+ and Fe 3+ , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Aiming at the implementation of {Fe(NO) 2 } 10 -reduced DNICs [Et 4 N][( Me DDB)Fe(NO) 2 ] and [(PMDTA)Fe (NO) 2 ] À as molecular electrocatalysts for HER in aqueous solution, however, cyclic voltammogram displaying the crossing character demonstrated that the in situ generated electrodeposited-film electrode is the dominant HER catalyst in aqueous condition. [47,[51][52][53] In this report, {Fe(NO) 2 } 10 DNIC [(2-AMP)Fe(NO) 2 ] (2-AMP = 2aminomethylpyridine) (1) was synthesized to serve as photocatalyst and precursor of active Fe 3 O 4 particles (major) working in concert with Fl (Fluorescein) and Et 3 N to build up the multi-component photocatalytic hydrogen evolution system in MeOH-H 2 O solution for light-driven hydrogen generation.…”
Section: à•mentioning
confidence: 99%
See 1 more Smart Citation